2020
DOI: 10.3390/genes11020149
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette and Cannabis Smoking Effects on GPR15+ Helper T Cell Levels in Peripheral Blood: Relationships with Epigenetic Biomarkers

Abstract: Background: Smoking causes widespread epigenetic changes that have been linked with an increased risk of smoking-associated diseases and elevated mortality. Of particular interest are changes in the level of T cells expressing G-protein-coupled receptor 15 (GPR15), a chemokine receptor linked with multiple autoimmune diseases, including inflammatory bowel disease, multiple sclerosis and psoriasis. Accordingly, a better understanding of the mechanisms by which smoking influences variation in the GPR15+ helper T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
(90 reference statements)
0
15
0
Order By: Relevance
“…Because these individual differences may account for, or confound, associations with morbidity and mortality risk, and because they may have somewhat different impact on different aging indices, it may be useful to control for cell-type variation when comparing effects across different indices. Conversely, it should be noted that some of the association between smoking and health outcomes could be the result of effects of smoking on cell-type variation [41,42]. However, prior research with African Americans has not found that correcting for cell-type variation decreases the association of lifestyle factors such as smoking with accelerated aging indices of morbidity or mortality [30].…”
Section: Controlling Cell-type Variationmentioning
confidence: 99%
“…Because these individual differences may account for, or confound, associations with morbidity and mortality risk, and because they may have somewhat different impact on different aging indices, it may be useful to control for cell-type variation when comparing effects across different indices. Conversely, it should be noted that some of the association between smoking and health outcomes could be the result of effects of smoking on cell-type variation [41,42]. However, prior research with African Americans has not found that correcting for cell-type variation decreases the association of lifestyle factors such as smoking with accelerated aging indices of morbidity or mortality [30].…”
Section: Controlling Cell-type Variationmentioning
confidence: 99%
“…148 Cigarette and cannabis smoking have been shown to lead to hypermethylation of two CpGs located in GPR15 and AHRR genes in helper T cells, leading to increased number of GPR15 + CD3 + CD4 + cells in peripheral blood, a well-known marker for autoimmune diseases, including psoriasis. 149…”
Section: Smokingmentioning
confidence: 99%
“…In blood, the most prominent upregulation of GPR15 in PBMCs was found to be associated with chronic cigarette smoking [ 3 , 18 , 38 , 39 , 40 ]. This upregulation slowly reverses over many years after cessation to the range of never smokers.…”
Section: Influences On Gpr15 Expressionmentioning
confidence: 99%
“…Surprisingly, the strongest association to GPR15 methylation in blood cells was related to smoking, particularly to chronic cigarette tobacco smoking as reviewed in [ 49 ]. In addition to cigarette smoking, cannabis smoking similarly mediates hypomethylation at cg19859270 in cells of the adaptive immune system accompanied by an excess in GPR15+ Th cells [ 39 ]. Whether combustion products from electronic cigarette smoking would exert a similar effect has not been studied to date.…”
Section: Influences On Gpr15 Expressionmentioning
confidence: 99%